A Primary Mediastinal Large B-Cell Lymphoma Patient With COVID-19 Infection After Intensive Immunochemotherapy: A Case Report - Li, Qiuhui; Zhu, Fang; Xiao, Yin; Liu, Tao; Liu, Xinxiu; Wu, Gang; Zhang, Liling (Frontiers in Oncology, 2020)
Background: The outbreak of coronavirus disease 2019 (COVID-19) had become a global public health event. Lymphoma patients need to be distinguished from general population because of their deficient immune status and intensive anti-tumor treatment. The impacts of cancer subtypes and treatment on COVID-19 infection are unclear. Case presentation: We here report a case of primary mediastinal large B cell lymphoma patient who infected with COVID-19 after intensive immunochemotherapy (DA-EPOCH-R). The patient developed a neutropenic fever during chemotherapy, and fever was persistent although antibiotics were used. Initial chest CT was negative, and the patient received throat swab test since the second CT showed evidence of pneumonia. With the treatment of Arbidol Hydrochloride and LianHuaQingWen capsule, his COVID-19 was cured. Conclusions: To the best of our knowledge, this is the first report focusing on COVID-19 infection in lymphoma patient with intensive immunochemotherapy. For those patients being treated with immunochemotherapy in epidemic area, reduced dose intensity of intensive chemotherapy should be considered, and the effect of immunotherapy, such as rituximab, on COVID-19 infection should be concerned. The impacts of anti-cancer treatment on COVID-19 infection need further exploration.